The Inner Life of Democracy: Learning in Deliberation between the Police and Communities of Color. Issue 1 (27th June 2018) - Wahl, Rachel
ABSTRACT: Deliberation has become a defining ideal of democratic theory, and learning is central to robust deliberation. It is challenging for people to learn from each other, however, in contexts of inequality and deep social cleavages — though this is precisely when such learning is most needed. The political theorist Danielle Allen has argued that the cultivation of "political friendships" and the development of verbal empowerment can mitigate the negative effects of difference and inequality in such settings. In this essay, Rachel Wahl uses her fieldwork on deliberation between police and communities of color to illuminate the challenges that are frequently encountered in efforts to adhere to Allen's aims and prescriptions, and also to consider the kind of learning that might make political friendship possible in the most challenging circumstances. Wahl shows how, in the context of divisive and unequal settings, people must develop the capacity not only to learn from those who are different from themselves but even from their sharpest critics. This requires a prior education that cultivates a kind of receptivity that can complement the long‐standing focus on agency and self‐expression in education for democratic citizenship. Her detailed account of the deliberative dynamics observed at a series of police–community fora reveals the political importance of inner life and of receiving an education that cultivates in individuals the disposition of receptive listening. Complicating deeply ingrained distinctions between the public and private spheres within a liberal society, it points to the value not only of cultivating skills, but also of shaping the person.